2010
DOI: 10.4103/1319-3767.61233
|View full text |Cite
|
Sign up to set email alerts
|

Study of respiratory disorders in endoscopically negative and positive gastroesophageal reflux disease

Abstract: Background/Aim:The relation between respiratory disorders and reflux symptoms has been debated since the beginning of the last century and the interest in this question has increased during the last few decades. This study aims to investigate the relation between specified respiratory disorders and reflux symptoms and examine the correlations between respiratory disorders and endoscopic findings in patients with gastroesophageal reflux disease.Patients and Methods:This study included 515 patients evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(30 reference statements)
1
17
1
2
Order By: Relevance
“…However, according to previous studies that have shown an impairment of gas exchange and/or impairment in spirometric functions [22,23], our study for the first time revealed significant differences in QS/QT values between both groups. In that context, our results suggest extension of pulmonary dead space as the potential new additional mechanism responsible for lung function damage in GERD patients.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, according to previous studies that have shown an impairment of gas exchange and/or impairment in spirometric functions [22,23], our study for the first time revealed significant differences in QS/QT values between both groups. In that context, our results suggest extension of pulmonary dead space as the potential new additional mechanism responsible for lung function damage in GERD patients.…”
Section: Discussionsupporting
confidence: 69%
“…Previously studies have revealed statistically significant differences in respiratory symptoms and functional tests in GERD patients, with a positive correlation with degree of gastroesophageal reflux severity [22,23]. Maher and Darwish reported serious loss of respiratory function in ERD compared with NERD patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the findings of our study, another study in Egyptian patients found that pulmonary manifestations were significantly higher in ERD patients than in NERD patients. 19 Although we report an association between high risk of OSA and NERD, we did not identify any obvious explanation for the mechanism of this association. We hypothesize that NERD patients may be at risk of extraesophageal symptoms.…”
Section: Discussioncontrasting
confidence: 56%
“…Out of this large pool, only 50 studies met our inclusion criteria with a focus on patients with reflux symptoms and provided sufficient information about sex distribution (Table 4). Twenty-five of the reports originated in Asia [37,, nine in Europe [99][100][101][102][103][104][105][106], seven in the US [56,[107][108][109][110][111][112], two in South America [113][114][115][116], four in African countries [117,118], and one in Canada [15], the studies reported data on 121 267 patients with 50.0 ± 1.2% women (range: 14.7-76.1%; P = 0.45). Considering the more recent emphasis of symptoms rather than endoscopic findings in the definition of GER, we examined time trends by separating studies into 3-year blocks, on the basis of their year of publication.…”
Section: Sex and Endoscopic Findings: Patient Studiesmentioning
confidence: 99%